Obesity and synergistic risk factors for chronic kidney disease in African American adults: the Jackson Heart Study. Issue 6 (30th August 2017) - Olivo, Robert E; Davenport, Clemontina A; Diamantidis, Clarissa J; Bhavsar, Nrupen A; Tyson, Crystal C; Hall, Rasheeda; Bidulescu, Aurelian; Young, Bessie; Mwasongwe, Stanford E; Pendergast, Jane; Boulware, L Ebony; Scialla, Julia J
ABSTRACT: Background: African Americans are at high risk for chronic kidney disease (CKD). Obesity may increase the risk for CKD by exacerbating features of the metabolic syndrome and promoting glomerular hyperfiltration. Whether other factors also affecting these pathways may amplify or mitigate obesity–CKD associations has not been investigated. Methods: We studied interactions between obesity and these candidate factors in 2043 African Americans without baseline kidney disease enrolled in the Jackson Heart Study. We quantified obesity as body mass index (BMI), sex-normalized waist circumference and visceral adipose volume measured by abdominal computed tomography at an interim study visit. Interactions were hypothesized with (i) metabolic risk factors (dietary quality and physical activity, both quantified by concordance with American Heart Association guidelines) and (ii) factors exacerbating or mitigating hyperfiltration (dietary protein intake, APOL1 risk status and use of renin–angiotensin system blocking medications). Using multivariable regression, we evaluated associations between obesity measures and incident CKD over the follow-up period, as well as interactions with metabolic and hyperfiltration factors. Results: Assessed after a median of 8 years (range 6–11 years), baseline BMI and waist circumference were not associated with incident CKD. Higher visceral adipose volume was independently associated with incident CKD (P   =   0.008) in a nonlinear fashion, but this effect was limited to those with lower dietary quality (P   =   0.001; P-interaction = 0.04). In additional interaction models, higher waist circumference was associated with greater risk of incident CKD among those with the low-risk APOL1 genotype (P   =   0.04) but not those with a high-risk genotype (P-interaction = 0.02). Other proposed factors did not modify obesity–CKD associations. Conclusions . Higher risks associated with metabolically active visceral adipose volume and interactions with dietary quality suggest that metabolic factors may be key determinants of obesity-associated CKD risk. Interactions between obesity and APOL1 genotype should be considered in studies of African Americans.